2015
DOI: 10.1099/vir.0.069872-0
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticosteroids trigger reactivation of human cytomegalovirus from latently infected myeloid cells and increase the risk for HCMV infection in D+R+ liver transplant patients

Abstract: Graft rejection in transplant patients is managed clinically by suppressing T-cell function with immunosuppressive drugs such as prednisolone and methylprednisolone. In such immunocompromised hosts, human cytomegalovirus (HCMV) is an important opportunistic pathogen and can cause severe morbidity and mortality. Currently, the effect of glucocorticosteroids (GCSs) on the HCMV life cycle remains unclear. Previous reports showed enhanced lytic replication of HCMV in vitro in the presence of GCSs. In the present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 90 publications
2
43
0
Order By: Relevance
“…In the absence of HIV-1, induction of replicating CMV has been shown to occur with the terminal differentiation of monocytes to myeloid dendritic cells, 49 and in vitro studies have demonstrated that monocyte to macrophage differentiation leads to production of infectious virus. [50][51][52] If HIV-1 infection activates monocytes and macrophages, 53 it is likely that CMV could be reactivated and replicate leading to an inflammatory response. In our study the association of CMV IgG with sCD14 within the HIV-1 viremic group, which was not present in the HIV-uninfected group, suggests that coinfection and long-term interaction of HIV-1 and CMV may lead to the development of serious non-AIDS events.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of HIV-1, induction of replicating CMV has been shown to occur with the terminal differentiation of monocytes to myeloid dendritic cells, 49 and in vitro studies have demonstrated that monocyte to macrophage differentiation leads to production of infectious virus. [50][51][52] If HIV-1 infection activates monocytes and macrophages, 53 it is likely that CMV could be reactivated and replicate leading to an inflammatory response. In our study the association of CMV IgG with sCD14 within the HIV-1 viremic group, which was not present in the HIV-uninfected group, suggests that coinfection and long-term interaction of HIV-1 and CMV may lead to the development of serious non-AIDS events.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that glucocorticoid plays a role in the HCMV kinetics of latency and reactivation, and that treatment with these compounds may increase the probability of HCMV-related complications post transplantation [11]. Our findings strongly suggest that glucocorticoid metabolism is deeply involved in HCMV life cycle and its related diseases in human body.…”
Section: Discussionmentioning
confidence: 64%
“…Next to clarify whether the DEXmediated transcriptional activation of the MIE promoter is dependent on GR, we examined the effect of RU486, a GR antagonist, on DEX-mediated transcriptional activation (Fig. 3F) [11]. In cells transfected with pMIEP-Luc-210, the DEX-mediated increase of the luciferase activity was suppressed by RU486.…”
Section: Identification Of the One 17 Bp-repeat Within Mie Enhancer Amentioning
confidence: 99%
See 1 more Smart Citation
“…23 Especially dexamethasone has been shown to cause CMV replication in vitro 24 and in vivo. 25 Cytomegalovirus is considered to be controlled by lymphocytes. 26,27 While the virus inhibits the function of T cells, 21 corticosteroids are lympholytic themselves, 28 likely increasing the risk for CMV reactivation.…”
Section: Goerig Et Al: Frequent Occurrence Of Cmv-encephalopathy Durmentioning
confidence: 99%